Analysis of Kendari Bay Sedimentation Distribution Pattern By Using High Resolution Image - Sufrianto; Andi Makkawaru Isazarni Jassin (International Journal of Management and Education in Human Development, 2022)
Specifically, the main problem to be investigated is how wide the spread of sedimentation in Kendari Bay is and the extent of delta formation due to changes in land function, with the aim that the government can make decisions in handling sedimentation in Kendari Bay effectively and efficiently. The analytical technique used in this research is a spatial analysis by means of Overlay using Series High-Resolution Image, each digitized for 3 Series using Geographic Information System (GIS) applications, High-Resolution Image has 3 Bands Red, Green, and Blue, to be able to find out the distribution pattern of sedimentation, it needs to be adjusted to the distribution from 2014, 2017 and 2021. Based on the results of the overlay analysis, the sedimentation distribution area of ​​Kendari Bay in 2014, 2017, and 2021 is 159.50 Ha, 258.15 Ha, and 280.90 Ha, respectively. The delta pattern is formed at the mouth of the Wanggu river with a delta area of ​​2014, 2017, and 2021, namely 17.97 Ha, 27.16 Ha, and 19.60 Ha respectively.